2020
DOI: 10.3389/fneur.2020.580540
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Interhemispheric Coherence in Cerebellar Kainic Acid-Induced Lateralized Dystonia

Abstract: The execution of voluntary muscular activity is controlled by the primary motor cortex, together with the cerebellum and basal ganglia. The synchronization of neural activity in the intracortical network is crucial for the regulation of movements. In certain motor diseases, such as dystonia, this synchrony can be altered in any node of the cerebello-cortical network. Questions remain about how the cerebellum influences the motor cortex and interhemispheric communication. This research aims to study the interhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…17 Direct cerebellar or striatal KA administration was shown to induce a wide range of behavioral alterations including epileptic seizures and dystonia, as well as impaired spatial learning and motor performance. [35][36][37] The cerebellum, one of the major structures of the hindbrain, plays a crucial part in the coordination of voluntary movements, maintaining balance, cognitive functions and motor learning activities. 38,39 KAinduced significant neuronal loss was observed in group KA for both 24 hours and 5 days subgroups in this study (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…17 Direct cerebellar or striatal KA administration was shown to induce a wide range of behavioral alterations including epileptic seizures and dystonia, as well as impaired spatial learning and motor performance. [35][36][37] The cerebellum, one of the major structures of the hindbrain, plays a crucial part in the coordination of voluntary movements, maintaining balance, cognitive functions and motor learning activities. 38,39 KAinduced significant neuronal loss was observed in group KA for both 24 hours and 5 days subgroups in this study (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Acquired injury to various components of a broad “dystonia network” have been reported to cause dystonia, with the cerebellum and basal ganglia emerging as critical nodes in this network[18, 59]. Previously, excitotoxic lesions of the cerebellar hemispheres or vermis, using kainic acid, have shown that injury to cerebellar components of the dystonia network can lead to dystonia[27, 59, 63, 79], while pharmacologic manipulations of the cerebellum in mouse models predisposed to dystonia also elicit dystonia[14]. Non-pharmacological lesioning of the cerebellar outflow tracts has not, to our knowledge, been reported in mice in the context of dystonia, although models of injury to the medial cerebellar nuclei and vermis have been reported in rats, using electrolytic charge delivery and mechanical suction, respectively[1, 8, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more importantly, pharmacologically induced dystonia models have been used to target specific anatomical structures in their investigation into dystonia. Using pharmacological lesions, rodent work has managed to elucidate key signaling biomarkers and mechanistic hallmarks of various dystonias in the cerebellum and basal ganglia [ 20 , 152 , 153 ]. Neychev et al first highlighted the cerebellar-basal ganglia circuit as being integral to the production of dystonic movements as cerebellum-originating dystonia was exacerbated by subclinical striatal lesions and alleviated by cerebellectomy [ 20 ].…”
Section: Rodent Models Of Functional and Acquired Dystoniamentioning
confidence: 99%
“…Fremont et al identified that in mice with ouabain-induced lesions the presence of dystonia was accompanied by persistent high-frequency bursts of cerebellar nuclear neurons, and restoration of the ouabain-blocked sodium channels alleviated the symptoms of dystonia as assessed with rotarod and observation assays [ 152 ]. Georgescu Margarint et al created an electromyographical setup that showed lateralized or vermal cerebellar dysfunction (due to kainic acid administration) ultimately triggered dystonia that was associated with a loss of connectivity in the corresponding cortical motor cortices ( Figure 3 ) [ 153 , 154 ], mirroring the human imaging studies in dystonic CP and task specific dystonias. Such studies have highlighted the evolutionary conservation of the dystonia network and shown that anatomic and circuit derived manipulations of the network can inform and confirm findings in the clinical population.…”
Section: Rodent Models Of Functional and Acquired Dystoniamentioning
confidence: 99%